The Use of Wordwall Media to Enrich Students Vocabulary Size in EFL Class - Fiska Nur Wulandari Zaen; Fauzi Miftakh; Indah Purnamasari (Peneliti.net, 2022)
This research aimed at finding out the process and perception of students in the use of wordwall media to enrich the size of students' vocabulary in the EFL class. The research used a qualitative case study method in conducting the research. Participants of this study is students of the seventh grade at Junior High School, students aged about 12-13 years who will be selected as research subjects. The data collection technique in this study is observation checklist and interview, the data analysis technique used in this study is a descriptive analysis method. The result of this study is The results showed that word wall media is the right medium in enriching students' vocabulary and helping students find out the names of objects in class according to their vocabulary and make it easier for students to memorize vocabulary. Students have no difficulty in using wordwall media in vocabulary learning, and they are very enthusiastic about feeling very happy, enjoy, not bored because the word wall media with colorful writing is pasted on the wall. Most seventh graders have positive responses about the use of word walls in learning vocabulary in junior high school. This can be seen based on pictures and words that are matched by students appropriately this media makes students very interested and easy to memorize some difficult vocabulary and also students' perception of word wall media is that students can enrich vocabulary and more easily understand it some vocabulary